Educating epistemological principles, virtues and research skills. Review on Marina Klimenko’s textbook “Research Methods in the Social Sciences” - Nowak, Ewa (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2021)
Improving university students’ research skills, research integ-rity and best standards for scientific excellence is crucial for all disciplines. Marina Klimenko, a senior lecturer at the Universi-ty of Florida, developed an innovative digital textbook entitled Research Methods in the Social Sciences (2020) with the focus on investigative psychology. The edition was powered by the e-learn-ing portal and published by Sentia Publishing. The author’s own epistemological and research expertise is combined here with her competence in higher education didactics. Klimenko’s textbook seems to be perfectly tailored for prospective researchers – and useful for various disciplines representing the social sciences and humanities.
Keywords: research excellence; scientific and research virtues; science-based learning; promoting students’ research competence; investigative psychology; advances in psychological education